Aerosol generating procedures in trauma and orthopaedics in the era of the Covid-19 pandemic; What do we know?. Issue 2 (April 2021) - Sobti, Anshul; Fathi, Mohamed; Mokhtar, Mohamed A.; Mahana, Karim; Rashid, Mustafa S.; Polyzois, Ioannis; Narvani, A. Ali; Imam, Mohamed A.
Abstract: Purpose: COVID-19 pandemic has created havoc all over the globe and spared no one regardless of status, gender, location and ethnicity. There were questions raised if trauma and orthopaedic (T&O) procedures actually generated aerosols? The need for a review of literature highlighting the nature and impact of aerosol generation within T&O surgery was noted. Methods: A comprehensive online search was performed for all published articles in the English language, evaluating AGPs in T&O surgery and the relevant personal protection equipment used. Results: The search strategy populated 43 studies. Six studies were identified as duplicates. The shortlisted 37 studies were screened and nine studies were included in the review. An additional four studies were included from the bibliography review. Conclusion: Most orthopaedic procedures are high-risk aerosol generating procedures (AGPs). Conventional surgical masks do not offer protection against high-risk AGPs. In the current era of COVID-19 pandemic, there is a significant risk to the transmission of infection to the theatre staff. For protection against airborne transmission, appropriate masks should be used. These need proper fitting and sizing to ensure full protection when used. Highlights: Surgical power tools lead to aerosol generation. Operating theatre high risk for COVID-19 disease transmission. Conventional surgical masks don't protect during high-risk AGPs. Need for air-purifying respirator masks. Proper fitting and sizing is essential.